Nation building through the corps - Abd Razak, Dzulkifli (2008)
ON June 21, two important events took place at two university campuses. At the Universiti Kebangsaan Malaysia campus, more than 1,000 students were involved in the passingout parade of the Reserve Officers Training Unit (Pasukan Latihan Pegawai Simpanan — Palapes). It had been part of the public universities cocurricular activities for more than two decades. At the Universiti Sains Malaysia campus, the Police Undergraduate Voluntary Corp had its passingout parade. More than 600 cadets were involved. The corp, better known as Suksis (Sukarelawan Kor Siswa Siswi) started in the late 1990s. The voluntary corps is now a cocurricular activity in 12 public universities.